The role of green social behavior in frugal innovation and entrepreneurial success: The moderating impact of knowledge management - Yu-Te Tu (Journal of Innovation & Knowledge (JIK), 2024)
Entrepreneurial success has become a necessary element of economic survival due to the current economic conditions and uncertainty worldwide. Thus, in this research, we explore green social behavior's impact on social, technological, and business innovation in a sample of Vietnamese manufacturing firms. Results of a PLS methodology reveal that green social behavior positively impacts the three aspects of innovation. The research aims to find the mediating and moderating aspects of social, technological, and business innovation and knowledge management. The outcomes confirm that only social and business (excluding technological) innovation effectively mediate the links between green social behavior and entrepreneurial success whereas knowledge management is a significant moderator. However, knowledge management insignificantly moderates the relationship between technological innovation and entrepreneurial success. This research guides policymakers in making policies related to entrepreneurial success using green social behavior, innovation, and knowledge management.
Keywords: Q55; L26; D80; 650; Knowledge management; Social innovation; Technological innovation; Business innovation; Entrepreneurial success; Green social behavior